Comparison of Fracture Resistance between Prefabricated and Fabricated Fiber Reinforced Post Systems on Different Post Canal Width - Widyastuti, Noor hafida; Hadriyanto, Wignyo; Mulyawati, Ema (Universitas Muhammadiyah Surakarta, 2016)
Background: Endodontic treated teeth are more susceptible to fracture. Correct restoration can minimize fracture risk, for example crown and post-core systems. Based on its manufacturing, Fiber Reinforced Composite (FRC) Post was divided into prefabricated and fabricated. The objective of this study was to evaluate the differences of fracture resistance between Prefabricated and Fabricated FRC Post systems on different post canal width. Method: The samples of this study were 28 premolars that were cut with 15 mm in length. The samples were treated with conventional endodontic method using gutta percha and resin sealer. The samples were divided into two groups and two sub-groups. The first two group was based on canal width consisting of 14 teeth each group with two different canal width (1.4 mm and 2.1 mm). Then, the first group was divided again into two subgroups based on the dowel use (Prefabricated post and Fabricated Post). Universal Testing machine was used to test the samples resistance. Result: This research showed that there were differences in fracture resistance on different post canal width. However, there were no fracture resistance differences between prefabricated post and fabricated post.